Knowledge of chronic kidney disease among University students - Ogundele, Samuel Babajide (My University, 2016)
The world's disease profile is changing and chronic diseases are now considered the leading cause of morbidity and mortality in the world. Chronic Kidney Disease is often asymptomatic, making individuals with the disease and also their health care provider unaware of it silent but yet threatening effect. Chronic Kidney Disease affects economically productive young adults between the ages of 20-50 years in sub Saharan Africa and knowledge of the disease has been observed to be the key point to successful prevention. The main aim of this study is to assess knowledge of university students on chronic kidney disease with the intention of understanding knowledge gaps and making recommendation for the formulation and implementation of educational programs. A non-experimental, descriptive, cross sectional survey design will be utilised in this study and simple random sampling method will be employed to select participants. The sample size comprises of 168 (n=168) participants selected from two male and female residences with an average of 42 sample from each of the residences. Data was collected by a means of self administered questionnaires developed by Chow et al. (2012). Data analysis was done using descriptive and inferential statistics. A response rate of 85.7% (n=144) was obtained. Out of a total of 144 (n=144), three quarter (75.01%; n=108) scored between 3 and 5 while more than half (60.42%) had good knowledge about kidney disease (≥ 4). The most common source of knowledge reported among respondents was high school (53.4%). There is no statistical significant relationship between demographic data and the overall knowledge of chronic kidney disease (all p >0.05) but Age and year of study was significantly associated with anatomy and symptoms while gender and family history of medical condition has a significant relationship with resource (p< 0.05). The research findings shows that knowledge about some aspect of chronic kidney disease is still lacking and majority indicated high school as there source of knowledge. Therefore, recommendations for nursing practice, policy development, and further research are proposed.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the award of Master of Science in Nursing Johannesburg, 2015